Educational Management Strategies in Improving Learning Quality in the Digital Era - Pajar Machmud; Shirley A. Padua Machmud; Alvin S. Sicat Machmud (SAJMR : Southeast Asian Journal of Management and Research, 2024)
The digital era has brought transformative changes to the educational sector, creating both opportunities and challenges in enhancing learning quality. This dissertation explores effective educational management strategies to improve learning outcomes through the integration of digital technologies. It examines key factors influencing the successful implementation of digital tools in education and provides policy recommendations to support this integration. The study employs a mixed-methods approach, combining qualitative and quantitative data to offer a comprehensive understanding of the impact of digital technologies on learning quality.